Thoracic aortopathy in Marfan syndrome overlaps with mechanisms seen in bicuspid aortic valve disease - Grewal, Nimrat; Dolmaci, Onur; Jansen, Evert; Klautz, Robert; Driessen, Antoine; Poelmann, Robert E. (Frontiers in Cardiovascular Medicine, 2023)
Background Thoracic aortopathy is a serious complication which is more often seen in patients with Marfan syndrome (MFS) and patients with a bicuspid aortic valve (BAV) than in individuals with a tricuspid aortic valve (TAV). The identification of common pathological mechanisms leading to aortic complications in non-syndromic and syndromic diseases would significantly improve the field of personalized medicine. Objective This study sought to compare thoracic aortopathy between MFS, BAV, and TAV individuals. Materials and methods Bicuspid aortic valve (BAV; n = 36), TAV (n = 23), and MFS (n = 8) patients were included. Ascending aortic wall specimen were studied for general histologic features, apoptosis, markers of cardiovascular ageing, expression of synthetic and contractile vascular smooth muscle cells (VSMC), and fibrillin-1 expression. Results The MFS group showed many similarities with the dilated BAV. Both patient groups showed a thinner intima (p < 0.0005), a lower expression of contractile VSMCs (p < 0.05), more elastic fiber thinning (p < 0.001), lack of inflammation (p < 0.001), and a decreased progerin expression (p < 0.05) as compared to the TAV. Other features of cardiovascular ageing differed between the BAV and MFS. Dilated BAV patients demonstrated less medial degeneration (p < 0.0001), VSMC nuclei loss (p < 0.0001), apoptosis of the vessel wall (p < 0.03), and elastic fiber fragmentation and disorganization (p < 0.001), as compared to the MFS and dilated TAV. Conclusion This study showed important similarities in the pathogenesis of thoracic aortic aneurysms in BAV and MFS. These common mechanisms can be further investigated to personalize treatment strategies in non-syndromic and syndromic conditions.